S7 High mortality from invasive pneumococcal pneumonia in the era of vaccine preventable disease. (15th November 2017) - Ferguson, K; Wilczynska, M
Abstract : Introduction and Objectives: Bacteraemia secondary to pneumococcal pneumonia is the most common presentation of invasive pneumococcal disease (IPD) and is associated with high mortality rates. 1 We conducted this study to evaluate differences in the process of care and outcome in patients with community-acquired invasive pneumococcal pneumonia (CAIPP) depending on age, co-morbidities and vaccination status. Methods: This was a retrospective study that analysed the data for patients with CAIPP who were hospitalised in 2016 at NHS Lanarkshire hospitals. Results: Forty-five of 60 patients with pneumococcal bacteraemia had IPD secondary to community-acquired pneumonia. The mean age of the patients was 61 years (17–101). The CURB 65 score was 0–1 in 55% patients, 2 in 12% and 3–5 in 33%. Overall 30 days mortality was 22%. The odds ratio of death within 30 days from CAIPP was 15.9 (95% CI: 1.8–140, p=0.012) among those who had any co-morbidity involving major organ (cardiac, respiratory, renal or liver failure). Thirty days mortality showed the strongest positive association with age (r=0.46, p=0.001) therefore patients were divided into two groups according to their age (Table 1 ). There was no difference between groups in time to reach diagnosis or initiate treatment. Within 4 hours of admission, a chest x-ray was obtained in 88% in Group 1 vs. 89% in Group 2 (p=NS), and the first dose of antibiotics was administered within 4 hours in 90% in Group 1 vs. 94% in Group 2 (p=NS). 79% patients in Group 2 had at least one major co-morbidity vs. 46% in Group 1 (p=0.012). Group 2 had significantly higher 30 days mortality than group 1, 47% vs 3.8% (p=0.002). In the Group 2, among deceased 44% (4 of 9) have not received pneumococcal vaccination. Only 4 of 26 patients in Group 1 were vaccinated against Streptococcus pneumonia. Conclusions: Clinical significance of IPP is underestimated in older people. Despite satisfactory initial assessment and prompt treatment mortality remains very high. That could be associated with the presence of co-morbidities and insufficient level of pneumococcal vaccination. Reference: Ludwig E et al . The remaining challenges of pneumococcal disease in adults. Eur Respir Rev 2012;21:57–65.